2008
DOI: 10.2320/matertrans.mra2008078
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of P-Type Heusler Compounds (Fe<SUB>2&minus;<I>x</I></SUB>Co<I><SUB>x</SUB></I>)(V<SUB>1&minus;<I>y</I></SUB>Ti<I><SUB>y</SUB></I>)Al

Abstract: We report on the effect of Co and Ti co-doping on the thermoelectric behavior of Fe 2 VAl based alloys. The doped alloys, (Fe 2Àx Co x )(V 1Ày Ti y )Al, with compositions x ¼ 0:01{0:07 and y ¼ 0:04{0:20 exhibit a p-type thermoelectric property when the total valence electron number is below 24. The co-doping of cobalt and titanium is believed to cause a substantial shift of the Fermi level from the center of the pseuodgap to a lower energy position. In particular, the alloy with x ¼ 0:03 and y ¼ 0:10 exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…One is to change its composition from stoichiometric to nonstoichiometric [3][4][5], and the other is to substitute a fourth element [6][7][8][9][10][11][12][13]. The methods proposed increase the absolute values of the Seebeck coefficient and reduce the electrical resistivity of Fe 2 VAl [3][4][5][6][7][8][9][10][11][12][13]. However, the thermal conductivity of Fe 2 VAl is comparatively large as a thermoelectric material; about 28 (Wm -1 K -1 ) at room temperature, resulting in the small ZT of Fe 2 VAl [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is to change its composition from stoichiometric to nonstoichiometric [3][4][5], and the other is to substitute a fourth element [6][7][8][9][10][11][12][13]. The methods proposed increase the absolute values of the Seebeck coefficient and reduce the electrical resistivity of Fe 2 VAl [3][4][5][6][7][8][9][10][11][12][13]. However, the thermal conductivity of Fe 2 VAl is comparatively large as a thermoelectric material; about 28 (Wm -1 K -1 ) at room temperature, resulting in the small ZT of Fe 2 VAl [14].…”
Section: Introductionmentioning
confidence: 99%
“…Three processes of Fe 2 VAl fabrication have been conventionally reported. The first one is melting method based on ingot metallurgy [3][4][5][6][8][9][10], the second one is mechanical alloying [11][12][13], and the third one is the combination of them [7]. All of the conventional processes require pure V as raw material to synthesize Fe 2 VAl, in which V has been industrially produced by a thermite reaction from V 2 O 5 and Al using strong exothermic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…While an effective valence electron count NCr of 6 for Cr is conventionally expected, a count of 7 fits very well with data from other doping studies on Fe2VAl. [9,11,[29][30][31][32][33][34][35][36][37][38][39][40] a useful and predictable tool in the careful crafting of Fe 2 VAl based compounds optimized for thermoelectrical applications.…”
Section: E Thermal Conductivitymentioning
confidence: 99%
“…Recently, the Fe 2 VAl alloy with fine microstructure was synthesized by mechanical alloying and pulse-current sintering, exhibiting an improved ZT value [11,12]. Furthermore, the thermoelectric properties of (Fe 1−x Co x ) 2 TiAl and p-type (Fe 2−x Co x )(V 1−y Ti y )Al alloys were also studied, which showed that the Co is a promising substituting element for Fe 2 VAl system [13,14]. However, the systematical effect of Co substitution for Fe 2 VAl remains a key issue for the thermoelectric property of Fe 2 VAl.…”
Section: Introductionmentioning
confidence: 98%